The prodigal daughter - Archer, Jeffrey, 1940- (Audio Renaissance, Coronet Books, 1982)
Florentyna Kane inherited from her immigrant father a vast hotel empire and a love for America. She finds fulfillment in love and family along the path to power, moving just a heartbeat away from her ultimate goal-- becoming the first female president of the United States. But she discovers that the price of power may be more than she is willing to pay.